Analisis Rasio Biaya Dana Pada (Studi Kasus) Laporan Keuangan PT BPD Jawa Timur - Situmorang, Febrina; Maulidyah, Syafrida; Putri, Rosalyta Rifany; Oktafia, Renny (CV. ITTC INDONESIA, 2024)
The role of banking currently has enormous power in the financial system, and has even become a key element in driving a country's economic progress. Banking institutions are business entities that operate in the financial sector or provide financial services. One form is the Regional Development Bank (BPD), which is owned by the provincial or district/city government of Indonesia. Fundamental role as a supporter of regional economic development by providing financial and banking services. BPD East Java is an example of a Regional Development Bank owned by the East Java Provincial Government. This research focuses on analyzing the financial reports of BPD East Java from 2020 to 2021